Providence of God Regarding the Universe : Part Three of the First Principal Part of The Universe of Creatures. - Auvergne, William of (Mediaeval philosophical texts in translation., 2007)
God's providence over the world posed a traditional set of questions for the medieval philosopher-theologian. In the third part of his first principal part of The Universe of Creatures, William of Auvergne argues that God's providence over creation extends to all things, the lowest as well as the highest. He tackles problems, such as pain, suffering, and other evils and faces questions, such as why the good often flourish in this life and whether providence imposes necessity on all things. He argues for human freedom and against fate, causal necessity, the world-soul, and the music of the sphe.